Numerical Study of Thermal Conductivity Effect on The Performance of Thermal Energy Storage (Journal of Engineering, 2022)
In this study, the effect of the thermal conductivity of phase change material (PCM) on the performance of thermal energy storage has been analyzed numerically. A horizontal concentric shell-and-tube latent heat thermal energy storage system (LHTESS) has been performed during the solidification process. Two types of paraffin wax with different melting temperatures and thermal conductivity were used as a PCM on the shell side, case1=0.265W/m.K and case2=0.311 W/m.K. Water has been used as heat transfer fluid (HTF) flow through in tube side. Ansys fluent has been used to analyze the model by taking into account phase change by the enthalpy method used to deal with phase transition. The numerical simulation assumptions were three-dimensional, transient, and laminar flow was used. The result for the PCMs of performance, temperature distribution, and liquid fraction during the discharge process were compared to each other. Furthermore, the Nusselt number was analyzed. The result showed that the increase in thermal conductivity of PCM reduces the time of the solidification process by 20%. The performance of LHTESS for case 2 is 63.2%, whereas for case1 is 54.6%.